Metabolic evaluation: who, when and how often. Issue 1 (January 2019) - De Coninck, Vincent; Keller, Etienne Xavier; Traxer, Olivier
Abstract : Purpose of review: To summarize recommendations of the guidelines of the American Urological Association and European Association of Urology, and our opinion on which urinary tract stone disease patients should be metabolically evaluated at which moment and how often. Recent findings: A standard metabolic evaluation should be performed in all stone formers to prevent recurrent disease. This includes a medical and lifestyle history, physical examination, basic urine and blood analysis, radiological examination and stone analysis. The latter should already be performed during surgery, especially when only a couple of fragments are sent for analysis. Supplementary, performing a 24-h urine analysis should be supported in all patients to understand the lithogenic process that will guide the according follow-up. When risk factors are found, an extended individualized metabolic evaluation should be performed to exclude underlying metabolic diseases and to start stone-specific recurrence prevention. Summary: Urologists should be trained in perioperative stone characterization, because it contains information of urinary environment at the times of stone formation and growth. The extensiveness and frequency of metabolic work-up and follow-up of stone formers should be tailored to the type of stone, severity of the disease, patient's comorbidities and medications.